Wernicke encephalopathy as a complication of hyperemesis gravidarum. - Pinillos Vilca, Alberto (2015)
If a pregnant 10 weeks hospitalized for hyperemesis gravidarum reported receiving replacement therapy with fluids and electrolytes, as well as pyridoxine, gravol, cimetidine and diazepam. The patient developed sleepiness, psychomotor agitation, disorientation, nystagmus, jaundice, ataxia and hypoesthesia to prevalence of lower limbs. Encefalopatís diagnosing Wernicke was made, giving replacement treatment with thiamine and achieving dramatic improvement. Emphasizing the rarity of presentation of this entity is made, classically related to chronic alcoholism, as well as the importance of early diagnosis and proper treatment to prevent evolution to Korsakoff's psychosis and even death.